Associated liver partition and portal vein ligation for staged hepatectomy: a review - Chan, Kai Siang; Low, Jee Keem; Shelat, Vishal G. (Translational Gastroenterology and Hepatology, 2019)
Outcomes of liver resection have improved with advances in surgical techniques, improvements in critical care and expansion of resectability criteria. However, morbidity and mortality following liver resection continue to plague surgeons. Post-hepatectomy liver failure (PHLF) due to inadequate future liver remnant (FLR) is an important cause of morbidity and mortality following liver resection. Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) is a novel two-staged procedure described in 2012, which aims to induce rapid hypertrophy of the FLR unlike conventional two-stage hepatectomy, which require a longer time for FLR hypertrophy. Careful patient selection and modifications in surgical technique has improved morbidity and mortality rates in ALPPS. Colorectal liver metastases (CRLM) confers the best outcomes post-ALPPS. Patients